The role of Neo-Ottomanism and its features in the context of the Second Karabakh War - S. M. Agamaliev (Проблемы постсоветского пространства)
The article is devoted to the study of Russia’s foreign policy and Turkey’s neo-Ottomanism during the Second Karabakh War, which lasted from September 27, 2020 to November 10, 2020. The author focuses on the events of autumn 2020 as a turning point in the long-term ethnopolitical and territorial conflict in the South Caucasus. The main attention dedicated to determining the factors influencing the positions taken by Russia and Turkey in the conflict, as the main external arbitrators and key regional players, as well as the consequences of the actions taken. The main reasons for Turkey’s active support of Azerbaijan are the conceptual foundations of neo-Ottomanism in combination with elements of pan-Turkism and the Muslim aspect, implying a desire for regional leadership in the South Caucasus and expanding its access to the Turkic world. Author identified the factors that influenced the absence of direct Russian intervention in the course of the war on the side of Armenia. (Maintaining the status quo of the conflict as the most acceptable for maintaining security in the region; agreeing with Azerbaijan’s legally justified claims to the territory of Nagorno-Karabakh from the point of view of international law; the importance of maintaining stable relations with Erdogan’s Turkey). Noteworthy the six-week war has changed the configuration of forces in the region. It led to the transformation of the poles of influence in the South Caucasus. Turkey has significantly strengthened its position as a regional factor, while Russia, on the contrary, has faced challenges and pro-Western development vectors among the former USSR countries.